The role of metronidazole on the establishment and persistence of oral candidosis - Veronica Quispe Yujra; Alexandre Prado Scherma; Juliana Campos Junqueira; Antônio Olavo Cardoso Jorge; Rosilene Fernandes Rocha (Universidade Estadual de Campinas, 2015)
The aim of this study was to study the effects of metronidazole on the establishment of oral candidosis and Candida albicans colonization in the oral cavity of rats. Forty-eight male rats, negative for yeasts in the oral cavity, were used in the study. The rats were inoculated with a suspension of Candida albicans and treated with metronidazole or plain water (control group). The rats of the candidosis experimental group were sacrificed 7, 15, or 30 days after inoculation and their tongues were analyzed by light microscopy. Colonization by Candida albicans was evaluated 1, 2, 5 and 7 days after inoculation and progressively at 15-day intervals, with a total of 18 collections. The results demonstrated the development of candidosis on the tongue dorsum was similar between the Control and Metronidazole groups for each sacrifice period. However, the colonization results showed that yeasts were recovered in the Metronidazole group in greater numbers than in the Control group after the 37th day of the experiment (6th collection). According this, the long term metronidazole therapy favored the colonization of C. albicans in the oral cavity of rats.